PERAN CAMAT DALAM PENYELENGGARAAN PEMERINTAHAN DAN PEMBANGUNAN DAERAH BERDASARKAN UNDANG-UNDANG NO.23 TAHUN 2014 (Studi Kasus di Kecamatan Mariso) - Pahlawan, Muh. iqra; Mustamin, Mustamin; Zulkifli Muhdar, Muhammad (Qawanin Jurnal Ilmu Hukum, 2022)
ABSTRAC This study aims to determine and analyze the role of the Camat in the Implementation of Government and Regional Development Based on Law No.23 of 2014 (Case Study in Mariso District. This empirical legal research method is basically a combination of normative legal approaches with the addition of various elements. Based on the results of this study, it can be concluded that the role of the Camat in Mariso District has been carried out in accordance with Law Number 23 of 2014 Article 225, which in the contents of Article 225 is carried out, namely coordinating community empowerment activities by involving all existing elements. in Mariso Subdistrict, coordinate efforts to maintain peace and public order by actively coordinating with the Polsek and Danramil, coordinating the implementation and enforcement of Regional Regulations and Regional Regulations where the active socialization of regional regulations and local regulations in the community cooperates with the Makassar City DPRD and implementing its implementation, coordinating the maintenance of public service infrastructure and facilities with the active work programs of the Mariso District such as garden maintenance, Clean Canal Program (PROKASIH), Clean-Up Mosques (BBM), Normalization of Drainage, coordinating the implementation of government activities carried out by Regional Apparatus in The sub-district, in coordination with the relevant offices, fosters and supervises the implementation of village and/or kelurahan activities, actively evaluating the performance of each kelurahan. One of the factors that support the running of the government system is Mariso Subdistrict, which always has regular evaluations and coaching so that the apparatus knows the tasks that must be done to increase the awareness of the apparatus, while the regulatory factors are set out in standard operating procedures (SOPs) and service standards as instructions for the service process. to society. Meanwhile, the obstacle faced in the last few years is the reduction in human resources available every day in the office with the division of the workday schedule to enter the office and the rest working from home (WFH) during the pandemic. ABSTRAK Penelitian ini bertujuan untuk mengetahui dan menganalisis Peran Camat Dalam Penyelenggaraan Pemerintahan Dan Pembangunan Daerah Berdasarkan Undang-Undang No.23 Tahun 2014 (Studi Kasus di Kecamatan Mariso. Metode penelitian hukum empiris ini pada dasarnya ialah penggabungan antara pendekatan hukum normatif dengan adanya penambahan dari berbagai unsur-unsur empiris. Berdasarkan hasil penelitian ini adalah maka dapat ditarik kesimpulan Peran Camat di Kecamatan Mariso telah terlaksana sesuai dengan Undang - Undang Nomor 23 Tahun 2014 Pasal 225, yang dimana dalam isi pasal 225 dijalankan yaitu mengoordinasikan kegiatan pemberdayaan masyarakat dengan melibatkan seluruh elemen yang ada di Kecamatan Mariso, mengoordinasikan upaya penyelenggaraan ketenteraman dan ketertiban umum dengan aktif berkordinasi bersalam Polsek dan Danramil, mengoordinasikan penerapan dan penegakan Perda dan Perkada yang dimana aktifnya sosialisasi perda dan perkada di masyarakat bekerja sama dengan DPRD Kota Makassar dan menjalankan penerapannya, mengoordinasikan pemeliharaan prasarana dan sarana pelayanan umum dengan aktifnya program kerja Kecamatan Mariso seperti pemeliharaan taman, Program Kanal Bersih (PROKASIH), Bersih-Bersih Masjid (BBM), Normalisasi Drainase, mengoordinasikan penyelenggaraan kegiatan pemerintahan yang dilakukan oleh Perangkat Daerah di Kecamatan dengan berkordinasi bersama Dinas terkait, membina dan mengawasi penyelenggaraan kegiatan Desa dan/atau kelurahan aktifnya mengevaluasi kinerja disetiap kelurahan. Faktor yang mendukung jalannya sistem pemerintahan dengan baik salah satunya adalah Kecamatan Mariso selau adanya evaluasi dan pembinaan secara rutin sehingga aparatur mengetahui tugas yang harus dikerjakan untuk meningkatkan kesadaran aparatur, adapun faktor aturan ditetapkan dalam standar operasional prosedur (SOP) dan standar pelayanan sebagai petunjuk proses pelayanan ke masyarakat. Sedangkan hambatan yang di hadapi bebrapa tahun terakhir adalah berkurangnya SDM yang ada disetiap hari kantor dengan adanya pembagian jadwal hari kerja untuk masuk kantor dan sisanya kerja dengan work from home (WFH) selama masa pandemi.